The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/catal6030033
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Reforming over Cobalt Catalysts Prepared from Fumarate Precursors: TPD Investigation

Abstract: Temperature-programmed desorption (TPD) was employed to investigate adsorption characteristics of CH 3 OH, H 2 O, H 2 , CO 2 and CO on cobalt-manganese oxide catalysts prepared through mixed Co-Mn fumarate precursors either by pyrolysis or oxidation and oxidation/reduction pretreatment. Pyrolysis temperature and Co/Mn ratio were the variable synthesis parameters. Adsorption of methanol, water and CO 2 was carried out at room temperature. Adsorption of H 2 and H 2 O was carried out at 25 and 300˝C. Adsorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Mixed cobalt-manganese oxides were investigated by Papadopoulou et al [6][7][8]. They employed in-situ XRD to identify the evolving crystalline phases at various stages of pyrolysis of cobalt-manganese gluconate or fumarate precursors and concluded the formation of MnO and metallic Co phases at 550°C due to the thermal decomposition of the fumarate precursor, whereas the decomposition of gluconate precursor above 200°C did not lead to the formation of crystalline phases before 650°C.…”
Section: Structure and Characterization Of Metallic Co Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed cobalt-manganese oxides were investigated by Papadopoulou et al [6][7][8]. They employed in-situ XRD to identify the evolving crystalline phases at various stages of pyrolysis of cobalt-manganese gluconate or fumarate precursors and concluded the formation of MnO and metallic Co phases at 550°C due to the thermal decomposition of the fumarate precursor, whereas the decomposition of gluconate precursor above 200°C did not lead to the formation of crystalline phases before 650°C.…”
Section: Structure and Characterization Of Metallic Co Nanoparticlesmentioning
confidence: 99%
“…Thus, reforming of both alcohols took place under comparable conditions at temperatures in the range of 400-450°C. The advantages of the proposed method of catalyst preparation were the formation of the reduced active state of the catalysts in a single step and the existence of residual carbon, which hindered sintering and excessive particle growth under synthesis and reaction conditions [6][7][8] polyhedral architectures and showed that they exhibited high discharge capacities for many discharge/charge cycles, due to their porous structure [18]. Yuan et al synthesized nanosized Co 3 O 4 and concluded that the advantage of this material over carbon was due to its higher capacity per unit volume (7.5 times in comparison to carbon) and that the particle size affected its electrochemical properties (the optimum average particle size was 37 nm) [19].…”
Section: Applications Of Cobalt-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption characteristics of methanol and its reforming products over Co-Mn catalysts were systematically investigated by Papadopoulou E. and Ioannides T. [7] through temperature-programmed desorption (TPD) studies. The influence of various parameters, in relation to the synthesis procedure and the Co/Mn ratio, into adsorptive properties was systematically explored in order to gain insight into the structure-activity relationships.…”
Section: Contribution Highlightsmentioning
confidence: 99%
“…It consists of 14 high-quality papers, involving: a comprehensive review article on the surface analysis techniques that can be employed to elucidate the phenomenon of electrochemical promotion in catalysis [3]; two theoretical studies (Density Functional Theory, DFT) on H 2 O dissociation and its implications in catalysis [4,5]; two mechanistic studies by means of temperature-programmed desorption/surface reaction (TPD/TPSR) and/or operando spectroscopy on N 2 O formation over NO x storage-reduction (NSR) catalysts [6] and on methanol reforming over cobalt catalysts [7]; two articles on H 2 production by the steam reforming of ethanol [8] or diesel [9] over transition metal-based catalysts; two articles on the production of commercial fuels by Fisher-Tropsch synthesis [10,11]; two articles on Au-catalyzed CO oxidation [12] and preferential CO oxidation [13]; and three experimental investigations regarding the structure-activity correlation of NO oxidation to NO 2 over Mn-Co binary oxides [14], cyclohexene oxidation on TiZrCo mixed oxides [15] and alkene epoxidation on silica nanoparticles [16].…”
Section: This Special Issuementioning
confidence: 99%